Effect of Heat Stress on Behavior, Physiological and Blood Parameters of Goat (Progressive Agriculture, 2013)
The research was conducted to study the effect of heat stress on behavior, some physiological and blood parameters with nine goats of almost similar in age, sex and weight into three groups. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) heat exposure. Temperaturehumidity index (THI) value was calculated as 28.17 which indicate the experimental animals were in extreme severe heat stress. Skin and rectal temperature had no significant differences among the treatment groups but respiration/panting and pulse rate were increased with the increased of heat stress from T0 to T8 group (P